2018
DOI: 10.1029/2018gl077719
|View full text |Cite
|
Sign up to set email alerts
|

On the Anthropogenic Impact on Long‐Term Evolution of Noctilucent Clouds

Abstract: Little is known about climate change effects in the transition region between the Earth's atmosphere and space, roughly at 80–120 km. Some of the earliest observations in this region come from noctilucent clouds (NLC) at ∼83‐km altitude. There is a long‐standing dispute whether NLC are indicators of climate change. We use model simulations for a time period of 138 years to study the impact of increasing CO2 and H2O on the development of NLC on centennial time scales. Since the beginning of industrialization th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
97
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(110 citation statements)
references
References 47 publications
12
97
1
Order By: Relevance
“…This is also in line with model simulations, which demonstrate about zero trend in the NLC occurrence rate and small positive trend in the NLC brightness at middle and subpolar latitudes (Berger & Lübken, ; Lübken & Berger, ). At the same time, the found small secular statistically insignificant NLC trends contradict large trends modeled by Lübken et al () for the period of 1960–2008 at 55–61°N. NLCs demonstrate statistically significant negative response to solar activity, as anticipated from theoretical consideration due to photodissociation of water vapor by the Lyman α flux. If ozone forcing is introduced to the MRA of the NLC data, then it produces a minor effect on long‐term changes in NLC occurrence frequency and brightness.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This is also in line with model simulations, which demonstrate about zero trend in the NLC occurrence rate and small positive trend in the NLC brightness at middle and subpolar latitudes (Berger & Lübken, ; Lübken & Berger, ). At the same time, the found small secular statistically insignificant NLC trends contradict large trends modeled by Lübken et al () for the period of 1960–2008 at 55–61°N. NLCs demonstrate statistically significant negative response to solar activity, as anticipated from theoretical consideration due to photodissociation of water vapor by the Lyman α flux. If ozone forcing is introduced to the MRA of the NLC data, then it produces a minor effect on long‐term changes in NLC occurrence frequency and brightness.…”
Section: Discussionsupporting
confidence: 91%
“…About the same result has been obtained by Berger and Lübken (2015), who have calculated near zero and even negative trends in NLC occurrence frequency at middle and subpolar latitudes (50-55°N and 55-60°N) based on model simulations for 1961-2013. At the same time, the most recently published model by Lübken et al (2018) have demonstrated large positive trends in the IWC at the mesopause, NLC occurrence frequency, and NLC brightness at middle and subpolar latitudes (55-61°N) for the period of 1960-2008. The authors have concluded that "NLC are indeed a longterm indicator for climate change due to the increase of H 2 O caused by the oxidation of methane, whereas the growth of carbon dioxide mixing ratio is of secondary importance."…”
Section: Journal Of Geophysical Research: Atmospherescontrasting
confidence: 72%
See 3 more Smart Citations